시선추적 실험에 나타난 세대간 시지각 주의집중 특성 - 김종하 (한국디자인리서치, 2022)
본 연구는 남성 20대와 60대의 시선추적 실험과 분석을 통해 세대별 주시횟수, 주시빈도, 동공크기의 변화에 나타난 시지각 주의집중 특성을 정리하였다. 시선추적 실험 결과 얻어진 주시데이터를 코딩하는 과정에 피험자별 특성이 개입될 수 있다. 전체 피험자의 특성을 재정리하는 과정에 주의집중을 판정하는 과정을 포함시킴으로써 세대간 시각적 주의집중 차이 특성을 밝히고 있다. 복합문화공간 이미지에 대한 시선추적 실험을 실시하고, 획득한 데이터를 코딩하는 과정을 정리하여 제시하였다. 자체 개발된 프로그램을 통해 새로운 코딩방법을 제시하고 있으며, 그 과정을 명확히 하여 연구결과의 객관적 평가기준을 제시하였다. 연구결과는 다음과 같이 몇 가지로 정의할 수 있다. 첫째, 추세선(trend line)을 이용한 세대별 주시횟수의 비교에서 20대는 일정 시간동안 우세 주시횟수를 늘리는 피험자가 많지만, 그 후에 완만하게 감소하고 있다. 이에 비해 60대는 시간의 경과와 함께 더 많이 보는 것에 할애한 것을 알 수 있다. 둘째, 모든 세대에서 초기 주시시간에 주시빈도가 증가하는 경향은 같으나 60대는 계속 증가하다가 감소하는데 비해, 20대는 감소하다가 급 증가하는 경향에 있다. 이것은 연령에 따라서 해당 공간을 보는 방법에 차이가 있음을 의미하는 것으로 시선의 고정과 이동에서 세대간 차이가 확연함을 알 수 있는 근거가 될 수 있다. 셋째, 20대와 60대 모두 특정 시간까지는 동공이 커지지만 20대는 완만하게 작아지는데 비해 60대는 지속적으로 커지는 피험자가 많은 것이 특징이다. 이것은 60대가 실험공간에 대한 지속적인 ‘자극에 대한 신기함 등’이 20대에 비해 상대적으로 컸던 것으로 해석이 가능하다. In this study, the characteristics that have changes in the number of observations, observation frequency, and pupil size for each generation were summarized through eye-tracking experiments and analysis in their twenties and sixties. The characteristics of each subject may intervene in the process of coding observation data, therefore the characteristics of visual attentional concentration differences between generations are outlined by including the process of determining attentional concentration in the process of rearranging the characteristics of all subjects. The study results can be defined in the following ways. First, in comparison of the number of observations by generation using a trend line, the subjects in their twenties who increase the number of predominant observations for a certain period of time, but it slowly decreases after. However, it is able to recognize that the subjects in their sixties dedicate themselves to observing more with the passage of time. Second, in all the generations, the trend of increasing the observation frequency at the initial observation time is identical, but while the subjects in their sixties continue to increase and then decrease, the subjects in their twenties tend to decrease and then rapidly increase. This means that there is a difference in the way of observing the given space according to age, therefore it can be the basis for knowing that there is a clear difference between generations in fixation and movement of observation. Third, the pupils of the subjects in their twenties and sixties both enlarge until a certain time, but the pupils of the subjects in their twenties slowly decrease, whereas there are many subjects in their sixties that continue to enlarge. This can be understood as the fact that the subjects in their sixties had a relatively higher level of ‘novelty about stimulation’ about the experimental space compared to the subjects in their twenties. KCI Citation Count: 0